The relationship between throwing velocity with and without leg movements and isokinetic muscle strength in elite water polo players - Yapici, A.; Zeki Ozkol, M.; Ozcaldiran, B.; Ergun, M. (European Journal of Physical Education and Sport Science, 2017)
of this study is to analyze the relationship isokinetic strength that the elite water polo players produced with lower and upper limbs (with leg movements) and only upper limbs (without leg movements) and the velocity of the shoot. Eighteen elite male players of Turkish professional water polo first league aged between fifteen and thirty-three took part in the study voluntarily. The physical characteristics of the players were taken and throwing velocities of overhead, back hand and sweep throw were measured from position 2, 3, 4 and 6. Isokinetic strength measurements were made within different joint moves (trunk, shoulder, knee, hip). In two separate shooting protocols (with and without leg movements) the shooting velocity were measured in different positions. A significant difference was found between with and without leg movement in different throwing velocity shoots were recorded in different shooting positions (p<0.01). It was seen that the average of the velocity of with leg movements shoot was higher than the without leg movements shoot. In terms of shooting positions, 2nd position when the relationship between the velocity of with leg movement shoot and isokinetic muscle strength was considered, trunk flexion, shoulder extension, left hip abduction, left knee flexion as relevant p<0.05, a relationship with right knee extension was found (p<0.01). 3rd position, a positive relationship (p<0.05) was recorded between trunk flexion, shoulder flexion, left hip abduction, right knee extension and left knee flexion. In 4th position, between the with leg movement shoot and trunk flexion, shoulder flexion, right hip extension, left hip extension, right hip flexion, left hip flexion, right knee extension, left knee extension, left knee flexion and left hip abduction. A positive relationship (p<0.01) between with leg movement (back) shoots thrown from 6th and trunk flexion, shoulder extension, shoulder flexion, left hip extension, right hip flexion, left hip abduction, right knee extension and left knee extension. Also a positive relationship (p<0.05) between the with leg movement backhand shoots thrown in 6th position, and right hip extension and left hip flexion. A positive relationship (p<0.05) was seen between the shoots thrown from part 6th position with leg movement sweep shoots and trunk flexion and left hip extension. When the relationship between the velocity of without leg movement shoot and isokinetic strength is overviewed according to the positions, in 2nd position there is a relationship between without leg movement shoot and trunk flexion and shoulder extension, with the shoulder flexion a positive relationship was seen (p<0.01). In 3rd position, there is a positive relationship (p<0.01), was recorded in the trunk flexion, a positive relationship (p<0.05) was seen in shoulder extension and shoulder flexion. In 4th position, a positive relationship (p<0.01) was found with the trunk flexion. A positive relationship (p<0.01) was found with the without leg movement backhand shoots that were thrown from the 6th position and trunk flexion, shoulder extension, shoulder flexion. A positive relationship (p<0.05) was recorded with the without leg movement sweep shoots and trunk flexion and shoulder extension. In conclusion, the isokinetic strength produced by the lower and upper limbs` relation with the velocity of with leg movement shoots thrown from different parts was found. The isokinetic strength produced by the upper limbs` relation with the velocity of without leg movement shoots thrown from different parts was found. The isokinetic strength's (produced by the upper limbs) contribution to the velocity of the shoot in without leg movement shoot is higher than with leg movement shoots. The results of the study upper limbs strengths` (trunk flexion, shoulder flexion, shoulder extension) are more effective in the velocity of the shoot.